Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1941
DOI: 10.1152/ajplegacy.1941.134.2.258
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Steroids of the Adrenal Cortex and Ovary on Capillary Permeability

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1944
1944
1986
1986

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It has been demonstrated that oestrogen acts by making high-energy phosphate fuel available to the synthetic machinery already present in the cells (Villee, Hagerman & Joel, 1960;Jensen, 1962). It has also been shown that oestrogen-induced changes in the reproductive tract are preceded by enhanced permeability of the cell membrane and the capillaries (Freed & Lindner, 1941;Hechter, Krohn & Harris, 1942;Reynolds, 1949;Richter & Albrich, 1952), and that androgens and progesterone antagonize this effect . Since phagocytosis involves the passage of par -ticulate matter across the cell membrane, it seems probable that factors affecting cell membrane permeability will also affect the phagocytic process; similarly, factors affecting capillary permeability will probably facilitate the access of particulate matter to RE cells lying outside the circulation.…”
Section: Stilbenesmentioning
confidence: 99%
“…It has been demonstrated that oestrogen acts by making high-energy phosphate fuel available to the synthetic machinery already present in the cells (Villee, Hagerman & Joel, 1960;Jensen, 1962). It has also been shown that oestrogen-induced changes in the reproductive tract are preceded by enhanced permeability of the cell membrane and the capillaries (Freed & Lindner, 1941;Hechter, Krohn & Harris, 1942;Reynolds, 1949;Richter & Albrich, 1952), and that androgens and progesterone antagonize this effect . Since phagocytosis involves the passage of par -ticulate matter across the cell membrane, it seems probable that factors affecting cell membrane permeability will also affect the phagocytic process; similarly, factors affecting capillary permeability will probably facilitate the access of particulate matter to RE cells lying outside the circulation.…”
Section: Stilbenesmentioning
confidence: 99%
“…This assumption can not be held likely, however, since this change clearly does not occur in the heart of the controls, while it is known that cortisone decreases the capillary permeability [3,9,10,25,29,31]. The increase is less on cortisone administration, but it can similarly be demonstrated.…”
Section: Discussionmentioning
confidence: 95%
“…treated daily for l0 days with 10 mg cortisone (Adreson, Organon) s.c. [10]; 4. treated with 10 IU synthetic lysine vasopressin (Sandoz) s.c. [10]; 5. treated daily for 10 days with 0.02 mg synthetic depot ACTH, and on the tenth day with 10 IU synthetic lysine-vasopressin s.c. treated daily for l0 days with 10 mg cortisone (Adreson, Organon) s.c. [10]; 4. treated with 10 IU synthetic lysine vasopressin (Sandoz) s.c. [10]; 5. treated daily for 10 days with 0.02 mg synthetic depot ACTH, and on the tenth day with 10 IU synthetic lysine-vasopressin s.c.…”
Section: Methodsmentioning
confidence: 99%
“…) Many other features of normal and abnormal menstrual cycles point in the same direction. The increase in capillary permeability which occurs in the premenstrual phase of both normal and abnormal cycles (Brewer, 1938;Heilig and Hoff, 1924.;Benda, 1925 ;Petersen and Milles, 1926) might be caused by a premenstrual depression of adrenal activity, as cortical hormones have been shown to reduce capillary permeability (Menkin, 1942; Freed and Lindner, 1941; Shleser and Freed, 1942). Premenstrual hyperuricacidaemia with a sharp drop during menstruation and a secondary rise immediately after the period (Okey and Erikson, 1926) is also best explained by adrenocortical influence (Sprague et al, 1950) especially as the pre-and post-menstrual levels of ovarian hormones are so different from one another as to make an ovarian explanation unlikely.…”
Section: Discussionmentioning
confidence: 99%